Dental material
By loading zinc zirconium phosphate materials with zinc ions on zirconium phosphate, combined with titanium oxide or zirconium oxide and resin, the problem of discoloration and insufficient antibacterial properties of dental materials under thermal light exposure is solved, and antibacterial and aesthetic properties are achieved. Dual effect.
Patent Information
- Application Number
- CN202380045552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-05-31
- Publication Date
- 2025-01-17
AI Technical Summary
Existing dental materials are unstable under heat and light exposure, prone to discoloration, and lack antibacterial properties, resulting in bacterial adhesion and inflammation, affecting the stability and aesthetics of the implant.
Zinc phosphate material with zinc ions loaded on zirconium phosphate is used, combined with titanium oxide or zirconium oxide and resin, and has a NASICON type or α type crystal structure, with zinc ion loading of more than 3W%, and silver ion loading of less than 1W%. , used for implant material.
It realizes antibacterial and not easily discolored dental materials, inhibit bacterial adhesion and inflammation, and maintains excellent aesthetics and stability of dental supplies.
Smart Images

Figure BDA0005174674360000091 
Figure BDA0005174674360000121
Abstract
Description
Technical Field
[0001] The present disclosure relates to a dental material. Background Art
[0002] Conventionally, materials having excellent biocompatibility (such as titanium, titanium alloys, and zirconium oxide) have been used as implant materials. Unlike natural teeth, bacteria can easily penetrate between implants and the mucosa. Conventional implant materials lack antibacterial properties, allowing bacteria to adhere to the implant surface. This can lead to peri-implant inflammation, which can cause implants to fall out of the bone.
[0003] Patent Document 1 discloses an antibacterial dental resin capable of preventing bacterial adhesion and growth. The resin disclosed in Patent Document 1 contains 0.2 to 10% by mass of an antibacterial agent. Patent Document 1 discloses an antibacterial agent comprising silver or both silver and zinc supported on a zirconium phosphate carrier. Patent Document 1 discloses the use of an antibacterial dental resin in dental crowns.
[0004] Patent Document 2 discloses an oral hygiene product composition whose antibacterial properties remain unchanged even after heat treatment and the presence of water. The composition disclosed in Patent Document 2 incorporates an antibacterial ceramic, in which an antibacterial metal is supported on the ceramic, as a medicinal ingredient. Patent Document 2 discloses an antibacterial ceramic in which zinc is supported on a ceramic composed of zirconium phosphate. Patent Document 2 specifically discloses toothpaste, tooth powder, mouthwash, coating, and oral ointment as oral hygiene products. Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 8-119821 Patent Document 2: Japanese Patent Application Laid-Open No. 6-122617 Summary of the Invention Technical problem to be solved by the invention
[0006] However, the silver ions contained in the resin disclosed in Patent Document 1 are unstable against exposure to heat and light and are easily reduced to metallic silver. As a result, dental crowns using the resin disclosed in Patent Document 1 are prone to discoloration, potentially impairing their aesthetics. Patent Document 2 does not describe or suggest a dental material (such as an implant material) that is used in dental treatment and placed in the oral cavity for a long period of time.
[0007] In view of the above situation, the present disclosure sets as a technical problem the provision of a product having antibacterial properties and being less prone to discoloration. Means of solving technical problems
[0008] Specific means for solving the above technical problems include the following methods. <1> A dental material comprising zinc-loaded zirconium phosphate in which zinc ions are loaded on zirconium phosphate. <2> According to the <1> In the dental material, the zirconium phosphate has a NASICON-type crystal structure or an α-type crystal structure. <3> According to the <1> or <2> The dental material has antibacterial properties against at least one of dental caries bacteria (Streptococcus mutans) and oral bacteria (Porphyromonas gingivalis). <4> According to the <1> ~ <3> In any one of the dental materials, the amount of zinc ions supported is 3 W% or more relative to the total amount of the zinc-supported zirconium phosphate. <5> According to the <1> ~ <4> In any one of the dental materials, the silver ion loading amount of the zinc-supported zirconium phosphate is 1 W% or less. <6> According to the <1> ~ <5> The dental material according to any one of the preceding claims further contains at least one of titanium oxide and zirconium oxide or a resin. The dental material is used as a material for an implant. Effects of the Invention
[0009] According to the present disclosure, a dental material is provided which has antibacterial properties and is less likely to discolor. DETAILED DESCRIPTION
[0010] In the present disclosure, a numerical range expressed using “to” means a range including the numerical values described before and after “to” as the lower limit and the upper limit. In the present disclosure, when a plurality of substances corresponding to each component are present in a composition, the amount of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified. In the numerical ranges described in stages in this disclosure, the upper limit or lower limit described in one numerical range may also be replaced by the upper limit or lower limit of the numerical range described in other stages. In the numerical ranges described in this disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the Examples. In the present disclosure, a combination of preferred aspects is a more preferred aspect. In the description of a group (atomic group) in the present disclosure, the description not describing substitution and unsubstituted encompasses the case of a group having no substituent and a group having a substituent.
[0011] (1) Dental materials The dental material disclosed herein contains zinc-loaded zirconium phosphate in which zinc ions are loaded on zirconium phosphate.
[0012] In the present disclosure, "dental materials" refer to all materials used in dental treatment and placed in the oral cavity for a long period of time (e.g., more than 1 day). Dental materials include implant materials, crown materials (e.g., crown resins, artificial teeth, etc.), dental filling materials (e.g., composite resins, root canal filling materials, bonding materials, etc.), dental adhesives (e.g., resin cements, orthodontic adhesives, etc.), pit and fissure sealants, coating materials, crown and bridge inlay resins, abutment building materials, denture base resins, and denture base repair resins. Dental materials do not include materials that are not placed in the oral cavity for a long period of time (e.g., oral hygiene products described in Patent Document 2, etc.). The phrase “zinc ions are supported on the zirconium phosphate” means that the supported amount of zinc ions is 0.1 W% or more relative to the total amount of zinc-supporting zirconium phosphate. The method for measuring the amount of zinc ions loaded is the same as that described in the Examples.
[0013] The dental material disclosed herein has the aforementioned structure, resulting in antibacterial properties and a low discoloration resistance. This reduces the likelihood of bacteria attaching to dental products using the dental material disclosed herein. As a result, the dental material disclosed herein can suppress inflammation, such as peri-implantitis, while maintaining the excellent aesthetic qualities of the dental product. This effect is presumably based on the following reasons, but the present invention is not limited thereto. Zinc ions are relatively stable to heat and light exposure and are difficult to reduce to metallic zinc. Furthermore, zinc ions exhibit antibacterial effects. These results are speculated to contribute to the antibacterial properties and discoloration resistance of the dental material disclosed herein.
[0014] The form of the dental material is not particularly limited and can be appropriately selected depending on the intended use of the dental material. Examples include solids (e.g., powders and tablets), semi-solids (e.g., gels and pastes), and liquids (e.g., solutions and dispersions).
[0015] (1.1) Zinc-loaded zirconium phosphate The dental material contains zinc-loaded zirconium phosphate.
[0016] The zinc-supported zirconium phosphate comprises zirconium phosphate and zinc ions supported on the zirconium phosphate.
[0017] The form of the zinc-supported zirconium phosphate is not particularly limited and may be, for example, particles.
[0018] The content of zinc-supported zirconium phosphate is not particularly limited and is appropriately selected depending on the application of the dental material. It is preferably 0.001 to 70 W%, more preferably 0.01 to 50 W%, based on the total amount of the dental material.
[0019] (1.1.1) Zirconium phosphate Zirconium phosphate has excellent biocompatibility and functions as a carrier of zinc ions.
[0020] The form of zirconium phosphate is not particularly limited, and may be, for example, particles. The raw material of zirconium phosphate is, for example, zirconium phosphate powder (hereinafter referred to as “zirconium phosphate powder”). The median particle size of the zirconium phosphate powder is not particularly limited and is appropriately selected depending on the application of the dental material. It is preferably 0.1 to 5 μm, more preferably 0.1 to 4 μm, further preferably 0.2 to 3 μm, and particularly preferably 0.3 to 2 μm. Considering the processability of dental products, not only the median particle size but also the maximum particle size of the zirconium phosphate powder is important. The maximum particle size of the zirconium phosphate powder is not particularly limited and is appropriately selected depending on the intended use of the dental material, but is preferably 10 μm or less, more preferably 6 μm or less, and even more preferably 4 μm or less. The median diameter is measured on a volume basis using a laser diffraction particle size distribution.
[0021] The crystal structure of zirconium phosphate is not particularly limited and may be amorphous or crystalline (for example, α-type crystal structure, β-type crystal structure, γ-type crystal structure, and NASICON-type crystal structure). Among them, from the viewpoint of improving the antibacterial properties of the dental material, zirconium phosphate preferably has a NASICON-type crystal structure or an α-type crystal structure.
[0022] Hereinafter, zirconium phosphate having an α-type crystal structure is also referred to as “α-zirconium phosphate.” Zirconium phosphate having a NASICON-type crystal structure is also referred to as “NASICON-type zirconium phosphate.”
[0023] (1.1.2) Zinc ion Zinc ions exhibit antibacterial effects.
[0024] The amount of zinc ions supported is not particularly limited, but is preferably 3 W% or more relative to the total amount of zinc-supporting zirconium phosphate. From the perspective of further improving the antibacterial properties of dental materials, the loading amount of zinc ions relative to the total amount of zinc-loaded zirconium phosphate is more preferably 3W% to 30W%, further preferably 3W% to 20W%, and particularly preferably 4W% to 20W%. The method for measuring the amount of zinc ions loaded is the same as that described in the Examples.
[0025] The method for loading zinc ions on zirconium phosphate is not particularly limited, and examples thereof include a method of exchanging zinc ions on zirconium phosphate and then performing a thermal decomposition treatment. Examples of the zinc ion exchange method include a method of immersing zirconium phosphate in an aqueous solution containing zinc sulfate.
[0026] (1.1.3) Other metal ions From the viewpoint of improving the antibacterial properties of dental materials, the zinc-supported zirconium phosphate may or may not support other metal ions in addition to zinc ions, within a range that does not hinder the effects of the present disclosure.
[0027] “No other metal ions are supported” means that the supported amount of other ions is 0.1 W% or less, including 0 W%, relative to the total amount of zinc-supported zirconium phosphate. The method for measuring the amount of other ions supported is the same as the method for measuring the amount of silver ions supported described in the Examples.
[0028] The other metal ions are at least one selected from the group consisting of silver ions, copper ions, tin ions, iron ions, cobalt ions, nickel ions, manganese ions, and barium ions.
[0029] In particular, from the viewpoint of further improving the antibacterial properties of the dental material, silver ions may be further loaded on the zirconium phosphate of the zinc-loaded zirconium phosphate. In the case where silver ions are further loaded on the zirconium phosphate, it is preferred to reduce the loading amount of the silver ions. By reducing the loading amount of the silver ions, discoloration of the dental material can be suppressed. In one embodiment of the present invention, the loading amount of the silver ions is preferably 1 W% or less, more preferably 0.5 W% or less, relative to the total amount of the zinc-loaded zirconium phosphate. Silver ions may not be loaded on the zirconium phosphate. Furthermore, it is preferred to reduce the silver content in the dental material as a whole. The silver content in the dental material is preferably 5 W% or less, more preferably 1 W% or less, and particularly preferably 0.5 W% or less.
[0030] (1.2) Metals, ceramics, and resins The dental material may contain at least one of metal, ceramic, and resin depending on the application of the dental material. Metals, ceramics, and resins may be any known materials used for dental products.
[0031] The dental material preferably further contains at least one of titanium oxide and zirconium oxide or a resin and is used as a material for an implant. Thus, the dental material can inhibit bacterial adhesion to the implant and can inhibit discoloration of the implant.
[0032] The implant comprises an implant body fixed to the bone, an abutment that can be attached and detached relative to the implant body, and an artificial crown fixed to the abutment. As materials for the implant body and the abutment, titanium oxide, zirconium oxide, titanium, and titanium alloys are generally used from the viewpoint of biocompatibility. As materials for artificial crowns, resins for artificial crowns are generally used. Examples of resins for artificial crowns include polyacrylates, polymethacrylates, polyolefins, polyamides, polyesters, polyethers, polynitrile, polyvinyl, cellulose resins, fluororesins, imide resins, and silicone resins.
[0033] When the dental material contains zinc-supported zirconium phosphate and a resin, the dental material is preferably used as a material for an artificial crown. Examples of the resin include the above-mentioned resins for artificial crowns. In the case where the dental material contains at least one of zinc-loaded zirconium phosphate, titanium oxide and zirconium oxide, at least one of titanium oxide and zirconium oxide is suitable for use as a material for abutment teeth and implant bodies, and zinc-loaded zirconium phosphate is suitable for use as a material for an antibacterial coating. The antibacterial coating covers at least a portion of the surface of at least one of the abutment teeth and the implant body. The antibacterial coating may also contain known components different from zinc-loaded zirconium phosphate, depending on the method for forming the antibacterial coating described later. The antibacterial coating is usually composed mainly of metal components and does not contain resin. The content of resin in the dental material used as the antibacterial coating may be less than 20W%, preferably less than 5W%.
[0034] The method for forming the antimicrobial film is not particularly limited and may be a known method, for example, a dry process and a wet process. In a dry process, the antimicrobial coating is formed by treating in a gas phase or in a vacuum. Specifically, examples of dry processes include physical vapor deposition (e.g., vacuum vapor deposition, ion plating, and sputtering), chemical vapor deposition (e.g., thermal CVD (Chemical Vapor Deposition), plasma CVD, and plasma CVD), hot-dip plating, spraying (e.g., flame spraying, arc spraying, and plasma spraying), coating, and dry surface modification methods (e.g., plasma surface modification and ion implantation). In a wet process, an antimicrobial coating is formed using a solution. Specifically, examples of wet processes include plating (e.g., electroplating, electroless plating, and electroforming), electropolymerization, sol-gel methods, Langmuir processes, coating, and wet surface modification methods (e.g., anodizing and chemical conversion treatment).
[0035] (1.3) Additives The dental material may contain additives as needed from the viewpoint of improving kneading processability into resins, other physical properties, and the like. Examples of additives include pigments, inorganic ion exchangers (such as zeolite), dyes, antioxidants, light stabilizers, flame retardants, antistatic agents, foaming agents, impact-resistant reinforcing agents, glass fibers, lubricants (such as metal soaps), moisture-proofing agents, extenders, coupling agents, nucleating agents, flowability improvers, deodorants, wood powder, mildew inhibitors, antifouling agents, rust inhibitors, metal powder, ultraviolet absorbers, and ultraviolet shielding agents.
[0036] (1.4) Target bacteria Dental materials exhibit antibacterial effects against bacteria including Escherichia coli and Staphylococcus aureus. The dental material preferably has antibacterial properties against at least one of caries bacteria (Streptococcus mutans) and oral bacteria (Porphyromonas gingivalis). This makes it difficult for caries bacteria and oral bacteria to adhere to the dental material. As a result, the dental material can inhibit the development of caries and further suppress inflammation such as peri-implantitis. [Example]
[0037] Hereinafter, the present disclosure will be specifically described with reference to Examples, but the present disclosure is not limited to the following Examples unless it exceeds the gist of the present disclosure.
[0038] [1] Manufacture of zirconium phosphate [1.1] Manufacturing Example 1 (Manufacturing of α-zirconium phosphate) In a 2L round-bottom flask, 1345mL of deionized water and 135g of 35% hydrochloric acid were added, and after adding 225g of a 20W% aqueous solution of zirconium oxychloride octahydrate containing 0.18W% of hafnium, 93g of oxalic acid dihydrate was added and dissolved. While stirring the solution thoroughly, 101g of 75W% phosphoric acid was added. After heating it to 98°C over 2 hours, it was refluxed while stirring for 12 hours. After cooling the reaction system, the obtained precipitate was filtered, washed thoroughly with water, and dried at 105°C under normal pressure to obtain the first zirconium phosphate. It was crushed using a rotor speed mill (16000rpm (revolutions per minute), 80μm mesh). Powder X-ray diffraction analysis of the first zirconium phosphate was performed under the following conditions. As a result, it was confirmed that the first zirconium phosphate was α-zirconium phosphate having an α-type crystal structure.
[0039] [1.2] Manufacturing Example 2 (Manufacture of NASICON-type zirconium phosphate) 1000 mL of deionized water was added to a 2L round-bottom flask, and after adding 366 g of a 20 W% aqueous solution of zirconium oxychloride octahydrate containing 0.18 W% of hafnium, 38 g of oxalic acid dihydrate was added and dissolved. While stirring the solution thoroughly, 123 g of 75 W% phosphoric acid was added. Next, 15 W% ammonia water was added dropwise until the pH reached 3. After heating it to 98°C over 2 hours, it was refluxed while stirring for 24 hours. After cooling the reaction system, the resulting precipitate was filtered, washed with water, and dried at 105°C under normal pressure to obtain ammonium zirconium phosphate having a NASICON-type crystal structure. It was crushed with a rotor mill (16000 rpm, mesh size 80 μm), and after heating the resulting powder to 750°C in an electric muffle furnace over 4 hours, it was calcined for 10 hours. Thus, a second zirconium phosphate was obtained. The powder X-ray diffraction analysis of the obtained second zirconium phosphate was performed under the following conditions. As a result, it was confirmed that the second zirconium phosphate was a proton-type zirconium phosphate having a NASICON-type crystal structure (hereinafter referred to as "NASICON-type zirconium phosphate").
[0040] [1.3] Powder X-ray diffraction The X-ray diffraction apparatus used was "D8 ADVANCE" manufactured by BRUKER. A Cu-encapsulated X-ray source was used, and an X-ray diffraction pattern was obtained using CuKα generated at an applied voltage of 40 kV and a current of 40 mA. Detailed measurement conditions are as follows.
[0041] [1.3.1] Measurement conditions X-ray source: Enclosed X-ray source (Cu ray source), 0.4×12mm 2 , Long FineFocus
[0042] [2] Dental materials [2.1] Example 1 (Introduction of Zn Ions into α-Zirconium Phosphate) 5 g of the α-zirconium phosphate obtained in Production Example 1, 41.7 g of zinc sulfate heptahydrate, and 453 g of pure water were added to a 500 mL beaker and stirred at 100° C. for 24 hours. The mixture was then filtered. The filtrate was then filtered and washed until the electrical conductivity of the filtrate was 100 μS / cm or less. The resulting powder was dried at 120° C. under normal pressure for 2 hours and pulverized in an agate mortar. This yielded a first powder (hereinafter also referred to as "α-zirconium phosphate Zn-substituted") (zinc-loaded zirconium phosphate). The mass of the first powder was measured. The first powder was dissolved in a mixture of nitric acid and hydrofluoric acid, and the Zn and Zr concentrations were measured by ICP emission spectrometry. These measurement results showed that the Zn introduced into the α-zirconium phosphate (the amount of zinc ions loaded) was 17 W% relative to the total amount of the Zn-substituted α-zirconium phosphate. 1 g of the Zn-substituted α-zirconium phosphate prepared by the above method, 0.1 g of sodium hexametaphosphate, 10 g of pure water, and 2 g of acrylic emulsion ("NW-7090" manufactured by Toagosei Co., Ltd.) were added and stirred with a stirrer to obtain a dispersion (dental material). This dispersion was applied onto a PET (polyethylene terephthalate) plate using a No. 28 bar coater and dried at 80° C. for 5 minutes to obtain an antibacterial test plate.
[0043] [2.2] Example 2 (Introduction of Zn Ions into NASICON-Type Zirconium Phosphate) 5 g of the NASICON-type zirconium phosphate obtained in Preparation Example 2, 1.6 g of zinc nitrate hexahydrate, and 100 g of pure water were added to a 100 mL beaker and stirred with a stirrer. The mixture was then evaporated to dryness at 100°C. The mixture was then ground in an agate mortar and calcined at 750°C for 4 hours. This yielded a second powder (hereinafter also referred to as "NASICON-type zirconium phosphate with Zn substitution") (zinc-supported zirconium phosphate). The mass of the second powder was measured. The second powder was dissolved in a mixture of nitric acid and hydrofluoric acid, and the Zn and Zr concentrations were measured by ICP emission spectrometry. These measurement results indicate that the Zn content (zinc ion loading) introduced into the NASICON-type zirconium phosphate was 7 wt% relative to the total amount of the Zn-substituted NASICON-type zirconium phosphate. A dispersion (dental material) and an antibacterial test plate were prepared under the same conditions as in Example 1, except that the NASICON-type Zn-substituted zirconium phosphate prepared by the above method was replaced with the Zn-substituted α-zirconium phosphate of Example 1.
[0044] [2.3] Comparative Example 1 (Unloaded zinc zirconium phosphate) A dispersion (dental material) and an antibacterial test plate were prepared under the same conditions as in Example 1, except that the Zn-substituted α-zirconium phosphate of Example 1 was not used.
[0045] [2.4] Comparative Example 2 (Introduction of Ag ions into NASICON-type zirconium phosphate) 5 g of the NASICON-type zirconium phosphate obtained in Preparation Example 2, 0.6 g of silver nitrate, and 100 g of pure water were added to a 100 mL beaker, stirred at 60°C for 2 hours, and then filtered. The filtrate was then filtered and washed until the electrical conductivity of the filtrate reached 100 μS / cm or less. The resulting powder was dried at 120°C under normal pressure for 2 hours, pulverized in an agate mortar, and calcined at 750°C for 4 hours. This yielded a third powder (hereinafter also referred to as "NASICON-type zirconium phosphate with Ag substitution"). The mass of the third powder was measured. The third powder was dissolved in a mixture of nitric acid and hydrofluoric acid, and the Ag and Zr concentrations were measured by ICP emission spectrometry. These measurement results indicate that the amount of Ag (silver ion loading) introduced into the NASICON-type zirconium phosphate was 3 wt% relative to the total amount of Ag substitution in the NASICON-type zirconium phosphate. A dispersion (dental material) and an antibacterial test plate were prepared under the same conditions as in Example 1, except that the α-zirconium phosphate with Zn substitution in Example 1 was replaced with a NASICON type zirconium phosphate with Ag substitution.
[0046] [3] Evaluation [3.1] Antibacterial test The viable counts of Escherichia coli, Staphylococcus aureus, oral bacteria, and dental caries bacteria on the antibacterial test plate were measured according to the method described in JIS Z 2801.
[0047] [3.2] Light resistance test A light resistance test was conducted by irradiating the antibacterial test plate with a carbon arc lamp for 8 hours, and the discoloration of the antibacterial test plate was visually observed and evaluated according to the following criteria. The results are shown in Table 1. The acceptable evaluation of the light resistance test was "A".
[0048] A: No color change was observed on the antibacterial test plate after the light resistance test compared to that before the light resistance test. B: Discoloration of the antibacterial test plate after the light resistance test was observed compared to that before the light resistance test.
[0049]
Table 1
[0050] In Table 1, "E. coli" indicates Escherichia coli, "S. aureus" indicates Staphylococcus aureus, "P. gingivalis" indicates oral bacteria (Porphyromonas gingivalis), and "S. mutans" indicates dental caries bacteria (Streptococcus mutans).
[0051] The dental material of Comparative Example 1 does not contain zinc-supported zirconium phosphate. Therefore, the number of viable Escherichia coli cells is 380,000 / cm 2 The viable count of Staphylococcus aureus is 2100 / cm 2 The number of viable oral bacteria is 18,000 / cm 2 The number of viable bacteria of dental caries is 4400 / cm 2 .
[0052] In Comparative Example 2, the dental material contained a NASICON-type zirconium phosphate Ag substitute, but did not contain zinc-loaded zirconium phosphate. Therefore, the number of viable Escherichia coli cells was 0 / cm 2 The number of viable Staphylococcus aureus cells was 0 / cm 2 The number of viable oral bacteria is 0 / cm 2 The number of viable bacteria of dental caries is 0 / cm 2 The evaluation result of the light resistance test was "B". These results show that the dental material of Comparative Example 2 is not a dental material having antibacterial properties and being less likely to discolor.
[0053] The dental materials of Examples 1 and 2 contain zinc-loaded zirconium phosphate in which zinc ions are loaded on zirconium phosphate but silver ions are not loaded. Therefore, the number of viable Escherichia coli cells is 30 / cm 2 The viable count of Staphylococcus aureus is 17 cells / cm 2 Below. The number of viable oral bacteria is 0 / cm 2 The number of viable bacteria of dental caries is 0 / cm 2 That is, the viable bacterial counts of Escherichia coli, Staphylococcus aureus, oral bacteria, and dental caries bacteria in Examples 1 and 2 were respectively reduced compared to Comparative Example 1. The evaluation result of the light resistance test was "A". These results show that the dental materials of Examples 1 and 2 have antibacterial properties and are less likely to discolor.
[0054] The disclosure of Japanese Patent Application No. 2022-094264 filed on June 10, 2022 is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, or technical standard was specifically and individually indicated.
Claims
1. A dental material comprising zinc-loaded zirconium phosphate in which zinc ions are loaded on zirconium phosphate. 2 . The dental material according to claim 1 , wherein the zirconium phosphate has a NASICON type crystal structure or an α type crystal structure.
3. The dental material according to claim 1, having antibacterial properties against at least one of caries bacteria (Streptococcus mutans) and oral bacteria (Porphyromonas gingivalis). 4 . The dental material according to claim 1 , wherein the amount of zinc ions supported is 3 W % or more relative to the total amount of the zinc-supporting zirconium phosphate. 5 . The dental material according to claim 1 , wherein the silver ion loading amount of the zinc zirconium phosphate is 1 W % or less.
6. The dental material according to any one of claims 1 to 5, further comprising at least one of titanium oxide and zirconium oxide or a resin. The dental material is a material for an implant.
Citation Information
Patent Citations
Composition for oral hygiene material
JP1994122617A
Antibacterial resin for dentistry
JP1996119821A
Device to understand reaction of severe physically / mentally- handicapped child or adult
JP2022094264A